Substrate mixing formulations for Citrus nursery management - Liberato, Erica Maria Sauer [UNESP]; Leonel, Sarita [UNESP]; Souza, Jackson Mirellys Azevedo; Napoleao, Gabriel Maluf [UNESP] (Univ Federal Mato Grosso, 2021)
The citrus seedling development is determined by several factors, including the physical and chemical qualities of the substrate, which affect the quality of field seedlings. The purpose of this study was to evaluate how the 'Swingle' citrumelo rootstock developed with different substrate formulations. The experiment was carried out in a seedling nursery from seeding to grafting, and six treatments were carried out: 60% peat moss, 30% fine grade horticultural vermiculite, 10% rice hulls; 60% peat moss, 30% super fine grade horticultural vermiculite, 10% rice hulls ; 50% peat moss, 30% fine grade horticultural vermiculite, 20% rice hulls ; 50% peat moss, 30% super fine grade horticultural vermiculite, 20% rice hulls ; 50% peat moss, 20% fine grade horticultural vermiculite, 30% rice hulls ; 50% peat moss, 20% super fine grade horticultural vermiculite, 30% rice hulls. When container transplanting was performed, the emergence percentage of seedlings was determined. Stem height, stem diameter, leaf number, area meter, root dry matter, leaf and stem dry matter, and quality index were measured on seedlings. All substrate formulations improved seedling development until grafting, except for the formulations with 30% rice hulls, which hampered seedling development in 'Swingle' citrumelo.
Keywords: [Citrus paradisi Macfad. Duncan grapefruit x Poncirus trifoliata (L.) Raf.]; peat moss; rice hulls; vermiculite